ESTUDO DE CASO: AVALIAÇÃO INSTITUCIONAL COMO INSTRUMENTO DE GESTÃO PARA DESENVOLVER A PRENDIZAGEM ORGANIZACIONAL NA IES PRIVADA - Travassos, Paula Francineti da Silva (2009)
The current study aims to investigate whether institutional self-evaluation may or not be considered an efficient tool to be used by Colleges and Universities in order to develop organizational learning processes and management knowledge. The work is based on SINAES MEC instructions and SWOT analysis and Porter s five forces. Data were based upon SWOT analysis. Furthermore, observations and documental analysis were done. The results of the research were arranged in tables, in order to show IES weaknesses and potentialities. The work also reveals that knowing their lack of strength and qualities, Colleges and Universities can improve their services as well give better conditions of working for their staff. It is also important to highlight that institutional self-evaluation requires encouragement to its practice.